2010
DOI: 10.1167/10.11.28
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles for frontal eye fields (FEFs) and intraparietal sulcus (IPS) in visual working memory and visual attention

Abstract: Cortical activity was measured with functional magnetic resonance imaging to probe the involvement of the superior precentral sulcus (including putative human frontal eye fields, FEF) and the intraparietal sulcus (IPS) in visual short term memory and visual attention. In two experimental tasks, human subjects viewed two visual stimuli separated by a variable delay period. The tasks placed differential demands on short-term memory and attention, but the stimuli were visually identical until after the delay peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…Szczepanski et al (2013), using an attentional task, demonstrated spatial asymmetries in FEF, an area within the same fronto-parietal network as IPS. In addition, at least one paper has demonstrated FEF involvement in VSTM (Offen et al, 2010), though not in a memory-load dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Szczepanski et al (2013), using an attentional task, demonstrated spatial asymmetries in FEF, an area within the same fronto-parietal network as IPS. In addition, at least one paper has demonstrated FEF involvement in VSTM (Offen et al, 2010), though not in a memory-load dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of sustained activity in the IPS is not consistent with other reports on visual working memory tasks (Curtis & D'Esposito, 2006; Schluppeck et al, 2006; Srimal & Curtis, 2008). However, our finding of specific patterns of activation in the absence of sustained activation might explain why sustained activation in the IPS during a visual working memory task has not always been replicated (Offen, Gardner, Schluppeck, & Heeger, 2010). …”
Section: Discussionmentioning
confidence: 92%
“…It is well established from studies in monkeys and humans that the posterior parietal cortex, and more specifically LIP, is crucial for spatial attention (Corbetta et al, 2002;Bisley and Goldberg, 2003;Owen et al, 2006). Attending to and tracking an object in space also involves working memory (Ricciardi et al, 2006;Offen et al, 2010), which may explain the DLPFC activation in our IOM task.…”
Section: Discussionmentioning
confidence: 93%